Qualitative renewal of economic education in the Republic of Belarus and the interdisciplinary research cluster “Belarusian Economic School” - S. Yu. Solodovnikov (Ekonomika Nauki)
The purpose of this study is to investigate the relationship between teaching modern political economy and qualitative renewal of economic education. To achieve this goal, we employ a system approach, subjective approach, institutional approach, and other general scientific methods and principles of cognition. The overall result of the study suggests that the creation of a positive national identity for Belarus is only possible through the implementation of modern political economy principles, which has led to the introduction of political economy as an academic discipline. However, this transition also highlighted the need to address several methodological challenges. First of all, it is necessary to visualize information in order to form a holistic picture of events occurring in Belarusian society and the world, influenced by internal political and economic factors, as well as the transformation of the global socio-economic environment and the modern world order. This helps to develop critical thinking and master the skills of analysing and assessing political and economic situation. It also enables making informed decisions in professional activities, as well as conscious choice of models of political and economic behavior in everyday life. The authoritative Belarusian Economic School is capable of fulfilling this important task.